Analisa Pengaruh Media Cooling Terhadap Umur Pahat Pada End Mill Cutter - Khoiri, Akhmad; Soebiyakto, Gatot; Farid, Akhmad (Widyagama University of Malang, 2023)
The process of cutting metal or scraping metal using a tool on a machine tool is one type of manufacturing process. In the process of working with machine tools itself, several processes are known such as turning, freis, drilling, grinding and scraping. The difference between these processes is the way of working and the products produced. While this test is about the turning process which is one of the metal scraping processes. The fixed variables used include lathe rotation (RPM) and depth of cut while the independent variable is the coolant used to cool the tool during the scraping process, namely synthetic coolant and seluble oil. By comparing the two coolants, it can be concluded that synthetic coolants have better performance when viewed from tool wear with a standard reference to the critical wear limit of 0.3-0.8 mm. The best performance is using Synthetic Fluid at RPM 650 with a depth of cut of 0.5 mm with a value of 0.05955 mm while the largest wear rate when using Seluble Oil liquid with RPM 1300 with a depth of cut of 1.5 with a value of 0.50495 mm. So it is highly recommended to use synthetic coolant with RPM.